Football players’ satisfaction with the quality of services provided by youth football coaching clubs - Allsabah, M. Akbar Husein; Sugito; Puspodari; Weda (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The level of satisfaction with the services provided to youth soccer coaching in Kediri, East Java, Indonesia is one form of success that has been carried out by the club in coaching youth soccer players. The satisfaction includes the player’s assessment of the services of the football player coaching club which includes aspects of satisfaction such as tangible, reliability, responsibility, assurance, and empathy. The purpose of this study was to assess football players’ satisfaction with the services of a youth soccer coaching club in Kediri, East Java, Indonesia. The study used a descriptive research method with a survey research approach. The subjects of this study were 335 respondents from a youth soccer player coaching club in Kediri, East Java, Indonesia. We used a questionnaire to collect the data. The questionnaire was in the form of questions with a Likert scale. The results showed that the majority of respondents’ assessment of each question item gave a good rating category. Based on the 19 question items given to the respondents, there are 58% or 11 items answering the satisfaction aspect with good results, then 32% or 6 items answering the satisfaction aspect with sufficient results, and 11% or 2 questions answering the satisfaction aspect with good results. very good. Based on the results of the study, it can be concluded that the level of player satisfaction with the services of youth football coaching clubs in East Java, Indonesia, is in the good category.